Introduction: From Beavers to Land: Building on Past Debates to Unpack the Contemporary Entanglements of Algonquian Family Hunting Territories - Chaplier, Mélanie; Scott, Colin (Anthropologica, 2018)
In 1986, Anthropologica published a special issue on Algonquian Family Hunting Territories (FHT) with diverse ethnographic research that overturned, grounded and reframed the earlier literature on the origins and the private-primitive communism property descriptions of Algonquian land tenure systems. The issue presented research developed with. for and in the emerging northern Indigenous political and legal struggles to continue to live on and govern their lands in the midst of rapid economic and state interventions. In this Introduction to the special issue, we provide a historical overview as well as a renewed framework for the analysis of Indigenous territoriality and governance which has been informed by the ways Algonquian peoples have continued to respond to the challenges they faced in the last thirty years. We describe the evolution of the Algonquian lives on the land and governance in the midst of resource exploitation and extraction, as well as important shifts within continually emerging Algonquian socialities.